Low-level and high-level modulations of fixational saccades and high frequency oscillatory brain activity in a visual object classification task - Kosilo, Maciej; Wuerger, Sophie M.; Craddock, Matt; Jennings, Ben J.; Hunt, Amelia R.; Martinovic, Jasna (Frontiers in Psychology, 2013)
Until recently induced gamma-band activity (GBA) was considered a neural marker of cortical object representation. However induced GBA in the electroencephalogram (EEG) is susceptible to artifacts caused by miniature fixational saccades. Recent studies have demonstrated that fixational saccades also reflect high-level representational processes. Do high-level as opposed to low-level factors influence fixational saccades? What is the effect of these factors on artifact-free GBA? To investigate this, we conducted separate eye tracking and EEG experiments using identical designs. Participants classified line drawings as objects or non-objects. To introduce low-level differences, contours were defined along different directions in cardinal colour space: S-cone-isolating, intermediate isoluminant, or a full-colour stimulus, the latter containing an additional achromatic component. Prior to the classification task, object discrimination thresholds were measured and stimuli were scaled to matching suprathreshold levels for each participant. In both experiments, behavioural performance was best for full-colour stimuli and worst for S-cone isolating stimuli. Saccade rates 200-700 ms after stimulus onset were modulated independently by low and high-level factors, being higher for full-colour stimuli than for S-cone isolating stimuli and higher for objects. Low-amplitude evoked GBA and total GBA were observed in very few conditions, showing that paradigms with isoluminant stimuli may not be ideal for eliciting such responses. We conclude that cortical loops involved in the processing of objects are preferentially excited by stimuli that contain achromatic information. Their activation can lead to relatively early exploratory eye movements even for foveally-presented stimuli.